Determinants of Birth Spacing and Effect of Birth Spacing on Fertility in Bangladesh (Dhaka University Journal of Science, 2013)
For the last few decades, demographers have directed considerable attention towards the study of human fertility through the analysis of birth interval data. This study examines the covariates of birth intervals and the effect of increased birth intervals on current fertility level in Bangladesh. Using the data of BDHS 2007, Cox Proportional Hazards model is used to determine the covariates of birth intervals. Mothers age at first birth, previous birth interval, mothers education and working status, mass media exposure appeared as the significant determinants of birth intervals. To estimate the tempo effect of birth interval on current fertility of Bangladesh, Bongaarts and Feeney method (1998) has been used. The tempo adjusted TFR was found to be 3.85, while the conventional TFR was 2.73 for the year 2005-06. This demonstrates that an increased effort to widen the spacing of births can effectively reduce the level of fertility in the future. Dhaka Univ. J. Sci. 61(1): 105-110, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15105